2011
DOI: 10.1021/jm200132q
|View full text |Cite
|
Sign up to set email alerts
|

17(R),18(S)-Epoxyeicosatetraenoic Acid, a Potent Eicosapentaenoic Acid (EPA) Derived Regulator of Cardiomyocyte Contraction: Structure–Activity Relationships and Stable Analogues

Abstract: 17(R),18(S)-Epoxyeicosatetraenoic acid [17(R),18(S)-EETeTr], a cytochrome P450 epoxygenase metabolite of eicosapentaenoic acid (EPA), exerts negative chronotropic effects and protects neonatal rat cardiomyocytes against Ca2+-overload with an EC50 ~1–2 nM. Structure-activity studies revealed a cis-Δ11,12- or Δ14,15-olefin and a 17(R),18(S)-epoxide are minimal structural elements for anti-arrhythmic activity whereas antagonist activity was often associated with the combination of a Δ14,15-olefin and a 17(S),18(R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 55 publications
2
61
0
2
Order By: Relevance
“…Increasing evidence obtained in mammalian systems suggests the existence of GPCRs (G protein-coupled receptors) that specifically interact with selected sets of epoxy and hydroxy metabolites derived from n−6 and n−3 PUFAs [52,66,67]. Supporting the hypothesis that 17,18-EEQ may interact with similar targets in mammals and C. elegans, we found that a metabolically robust synthetic analogue, developed to mimic the effect of 17,18-EEQ on cardiomyocyte contractility [20], was also effective in modulating the locomotive activity of C. elegans. Further genetic analysis of the components mediating the 17,18-EEQ effects in C. elegans may facilitate the search for the thus far unknown receptors of CYPeicosanoids.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Increasing evidence obtained in mammalian systems suggests the existence of GPCRs (G protein-coupled receptors) that specifically interact with selected sets of epoxy and hydroxy metabolites derived from n−6 and n−3 PUFAs [52,66,67]. Supporting the hypothesis that 17,18-EEQ may interact with similar targets in mammals and C. elegans, we found that a metabolically robust synthetic analogue, developed to mimic the effect of 17,18-EEQ on cardiomyocyte contractility [20], was also effective in modulating the locomotive activity of C. elegans. Further genetic analysis of the components mediating the 17,18-EEQ effects in C. elegans may facilitate the search for the thus far unknown receptors of CYPeicosanoids.…”
Section: Discussionsupporting
confidence: 75%
“…In mammals, CYP-eicosanoids act in an autocrine or paracrine manner and serve as second messengers of diverse hormones regulating the contractility of vascular smooth muscle cells and cardiomyoctes [20,60,61]. In C. elegans, 17,18-EEQ mediates the O2-ON response by increasing the activity of body muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both quantity and purity of prepared eicosanoid stock solutions were confi rmed by LC/MS/MS measurements (data not shown). The compound used as 17,18-EEQ agonist was synthesized as described previously ( 21 ). To prevent autoxidation, all stock solutions, except for neurohormones, were prepared in an oxygen evacuated nitrogen chamber.…”
Section: Chemicalsmentioning
confidence: 99%
“…[10] We have reported iridium-catalyzed synthesis of dialkylated ureas from ureas and alcohols. [11][12] The dialkylated ureas are important classess of biologically active compounds.However, the reaction required long reaction time (12 h). [13] Therefore, herein we wish to demonstrate that microwave irradiation significantly accelerated the process of the reaction.…”
Section: Introductionmentioning
confidence: 99%